Economic Crisis Recovery with Legal Policies by Governments (A Comparative Study between Indonesian, French, and Argentinian Law) - Arfandy, Muh Farhan; Rinata, Asfara Rachmad (Universitas Airlangga, 2025)
This article compares the legal policies implemented by France, Argentina, and Indonesia in addressing economic crises. The research method used in this study is doctrinal legal research, combined with a prescriptive-analytical approach, aims to provide recommendations for addressing specific issues and generate arguments, theories, or new concepts as solutions. The findings of this research indicate that France, through the Macron Law, seeks to overcome the economic crisis by reforming the labor market and implementing social policies. Meanwhile, Argentina addresses economic crises by referring to its Constitution, particularly Article 76 and Article 99(3), which provide the legal framework for the government to handle public emergencies and regulate the executive-legislative relationship in crisis policymaking. This is evident in Law 25.156 and Decree 1.019 of 1999, which govern competition protection. In Indonesia, the economic crisis triggered by the Covid-19 pandemic was addressed through the National Economic Recovery (PEN) policy, which relies on statutory authorization. Additionally, Indonesia has adopted a legislative model in responding to emergencies, a concept introduced by Tom Ginsburg and Mila Versteeg.